Population growth and land-use change among pastoral people: Local processes and continental patterns. Poster - Ellis, J.; Reid, Robin S.; Thornton, Philip K.; Kruska, Russell L. (International Rangeland Congress, Inc., 1999)
The question of whether the contentious situation at the Ngorongoro Conservation Area, Tanzania, engendered by human population growth, agricultural intensification and perceptions of proper and sustainable land use, is a prevalent problem on a broader continental scale is addressed.